Direction Dependent Electrical Conductivity of Polymer/Carbon Filler Composites - Kunz, Karina (Polymers (Basel), 2019)
The method of measuring electrical volume resistivity in different directions was applied to characterize the filler orientation in melt mixed polymer composites containing different carbon fillers. For this purpose, various kinds of fillers with different geometries and aspect ratios were selected, namely carbon black (CB), graphite (G) and expanded graphite (EG), branched multiwalled carbon nanotubes (b-MWCNTs), non-branched multiwalled carbon nanotubes (MWCNTs), and single-walled carbon nanotubes (SWCNTs). As it is well known that the shaping process also plays an important role in the achieved electrical properties, this study compares results for compression molded plates with random filler orientations in the plane as well as extruded films, which have, moreover, conductivity differences between extrusion direction and perpendicular to the plane. Additionally, the polymer matrix type (poly (vinylidene fluoride) (PVDF), acrylonitrile butadiene styrene (ABS), polyamide 6 (PA6)) and filler concentration were varied. For the electrical measurements, a device able to measure the electrical conductivity in two directions was developed and constructed. The filler orientation was analyzed using the ratio σ(in/th) calculated as in-plane conductivity σ(in-plane) (σ(in)) divided by through-plane conductivity σ(through-plane) (σ(th)). The ratio σ(in/th) is expected to increase with more pronounced filler orientation in the processing direction. In the extruded films, alignment within the plane was assigned by dividing the in-plane conductivity in the extrusion direction (x) by the in-plane conductivity perpendicular to the extrusion direction (y). The conductivity ratios depend on filler type and concentration and are higher the higher the filler aspect ratio and the closer the filler content is to the percolation concentration.